2030, the coming tumult : unlimited growth on a finite planet - Mosey, Richard M., 1950- (Algora Pub., 2009)
The short-term benefits of unlimited growth are driving the American economic and social model right off a cliff. The author shows how corporations drown out scientists and global elites prosper during economic collapse. He explores the role of monotheistic religions in abetting population growth and downplaying human agency in the current unprecedented crisis and charts the effects of increasing poverty, population migration, and social tension.